Pengaruh Periklanan Dalam Jaringan Terhadap Keputusan Pembelian Cottonink (Survei Pada Followers Instagram Cottonink) - Ramizah, Azaya Najmi; Utama, Raden Dian H; Amanah, Dita (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2025)
This research aims to obtain an overview and analyze the influence of online advertising on purchase decisions (a survey of Instagram followers of Cottonink in Bandung). The study employed a descriptive and verificative method with a quantitative approach. The population in this research consisted of 628,000 followers of Cottonink’s Instagram account, with a sample of 130 respondents selected using the purposive sampling technique. The research instrument tests included validity and reliability tests, while the data analysis technique applied was simple linear regression, assisted by IBM Statistical Product and Service Solutions (SPSS) version 26.0 for Windows. The findings of this study indicate that both online advertising and purchase decisions are categorized as good. Furthermore, online advertising has a positive and significant effect on purchase decisions.